2021
DOI: 10.3390/cancers13194950
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 Alterations Induce Acquired Dabrafenib Resistance in Association with Anaplastic Transformation in a Papillary Thyroid Cancer Patient

Abstract: BRAF-activating mutations are the most frequent driver mutations in papillary thyroid cancer (PTC). Targeted inhibitors such as dabrafenib have been used in advanced BRAF-mutated PTC; however, acquired resistance to the drug is common and little is known about other effectors that may play integral roles in this resistance. In addition, the induction of PTC dedifferentiation into highly aggressive KRAS-driven anaplastic thyroid cancer (ATC) has been reported. We detected a novel RAC1 (P34R) mutation acquired d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…EGFR and RAC1 upregulation may represent off-target resistance mechanisms in melanoma and thyroid cancer under BRAF inhibitors. 23,34 Epigenetic mechanisms, that modulate DNA methylation, histone, and chromatin structure, may also have a role in DT resistance, because they can promote differential expression of genes, which could be associated with a decreased efficacy of BRAF inhibitors, as observed in melanoma and NSCLC. 31 This study has several strengths that support its results: the review by the same expert pathologist, the closely (monthly) radiological follow-up by the same expert radiologist, the long-term follow-up of ATC to assess OS and PFS, the PET-CT validation of CR, and two contemporary ATC groups that reflect the local practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR and RAC1 upregulation may represent off-target resistance mechanisms in melanoma and thyroid cancer under BRAF inhibitors. 23,34 Epigenetic mechanisms, that modulate DNA methylation, histone, and chromatin structure, may also have a role in DT resistance, because they can promote differential expression of genes, which could be associated with a decreased efficacy of BRAF inhibitors, as observed in melanoma and NSCLC. 31 This study has several strengths that support its results: the review by the same expert pathologist, the closely (monthly) radiological follow-up by the same expert radiologist, the long-term follow-up of ATC to assess OS and PFS, the PET-CT validation of CR, and two contemporary ATC groups that reflect the local practice.…”
Section: Discussionmentioning
confidence: 99%
“…In patient 3, a pathogenic NRAS p.Q61K mutation, which probably represents an acquired off-target resistance mechanism to DT, was detected. 25,34 In patient 4, no new alterations were observed in the surgical specimen compared with baseline, by NGS, or by Sanger sequencing analysis of RAC1 and PTEN genes. No gene fusions in BRAF, ALK, RET, and NTRK were detected.…”
Section: Tumor Mutational Profiling Through Ngs and Sanger Sequencingmentioning
confidence: 96%
See 1 more Smart Citation
“…Referring to dabrafenib resistance levels, another study focused on an unexplored novel RAC1 (P34R) mutation acquired in BRAF. They reported an excessive EGFR /MET protein over-expression due to gene amplification in PTC cases that led to dedifferentiation enhancing their aggressive genotype/phenotype by increasing their metastatic potential (37). In contrast to successive responses in TKI-based therapeutic approaches, there are sub-groups of patients that lose clinical benefits after discontinuation of lenvatinib-based treatment (38).…”
Section: Anti-egfr/braf Tyrosine Kinase Inhibitor (Tki)-based Strateg...mentioning
confidence: 99%
“…Bagheri-Yarmand, Busaidy and colleagues characterized a metastatic PTC case that developed an acquired resistance to the BRAF inhibitor dabrafenib, demonstrating that this resistance is mediated, at least in part, by acquired alterations at RAC1 gene (encoding a GTPase), and perhaps the co-amplification of other genes within chromosome 7. The authors showed, by employing patient-derived cell lines and isogenic cell models, that RAC1 alterations enhance growth, invasion and signaling via phospho-PAK1, suggesting potential vulnerabilities for combinatorial therapies [ 12 ].…”
mentioning
confidence: 99%